Utility of gastric ultrasound in evaluating nil per os status in a child - Munlemvo, Dolly (Saudi J Anaesth, 2021)
Although rare, the aspiration of gastric contents can lead to significant morbidity or even mortality in pediatric patients receiving anesthetic care. For elective cases, routine preoperative practices include the use of standard nil per os times to decrease the risk of aspiration. However, patients may fail to adhere to provided NPO guidelines or other patient factors may impact the efficacy of standard NPO times. Gastric point-of-care ultrasound provides information on the volume and quality of gastric contents and may allow improved patient management strategies. We present a 4-year-old patient who presented for bilateral myringotomy with tympanostomy tube insertion, who was found to have evidence of a full stomach during preoperative gastric ultrasound examination. The use of preoperative gastric point-of-care ultrasound in evaluating stomach contents and confirming NPO times is reviewed and its application to perioperative practice discussed.